Gusjigang and Islamic Human Resource Management in Technology-Based Enterprises - Agus Supriyanto (Social Science Academic, 2024)
This study aims to analyze the actualization of the Gusjigang philosophy in strengthening human resource management and fostering an Islamic work environment in technology based enterprises in Kudus Regency, Indonesia. The research employed a qualitative approach using a descriptive analytical case study design. Informants were selected through purposive sampling and consisted of four business owners and six employees from technology based enterprises that had been operating for at least three years. Data were collected through in depth interviews, observation, and document analysis, and were analyzed using data reduction, data display, and conclusion drawing and verification techniques. The findings reveal that the three core values of the Gusjigang philosophy, namely gus (morality and integrity), ji (learning and spirituality), and gang (entrepreneurship and innovation), are highly relevant to contemporary human resource management practices. The gus value contributes to the development of a workplace culture grounded in trustworthiness, responsibility, and honesty. The ji value promotes a culture of continuous learning that supports both competency development and employees’ spiritual growth. Meanwhile, the gang value strengthens entrepreneurial orientation, creativity, and organizational innovation. The integration of these three values fosters an Islamic work environment that is productive, ethical, and sustainable. This study contributes to the development of the Indigenous Islamic Human Resource Management concept by demonstrating that local wisdom can serve as a strategic source of organizational values in managing technology based enterprises in digital era.